Fluorescence Spectroscopy Applied in the Identification of Lubricant Oils - Claudio Yamamoto Morassuti; Sandro Marcio Lima; Fabio Alencar dos Santos; Luis Humberto da Cunha Andrade (Orbital: The Electronic Journal of Chemistry, 2018)
In this work, we report the use of fluorescence spectroscopy to identify lubricant oils. Optical characterization was performed in four commercial lubricant oils that are used in reciprocating compressors. Mid-infrared absorption of samples indicates the presence of aromatic rings showing bands at 1605 cm-1 (C=C stretching) and 815 cm-1 (C–H stretch out of plane). UV-VIS absorption spectra show bands of di- and polyaromatic rings (around 230 nm and 260 nm, respectively). By exciting the samples at 360 nm, a broad emission band centered at 440 nm is observed, indicating that this excitation is appropriate to be used for the diagnosis of oil presence in the environment.